Using river flow management to improve wetland habitat quality for waterfowl on the Mississippi River, USA - Dugger, Bruce D; Feddersen, Jamie C (Wildfowl, 2013)
In an effort to improve wetland conditions on the highly regulated Upper Mississippi River, the U.S. Army Corps of Engineers conducted an experiment that involved using navigation dams to restore the stable, summer low water portion of the natural flow regime that would expose soil and permit establishment of moist-soil plant species. Plant response was measured and waterfowl surveys and behavioural observations were conducted to evaluate the ability of river flow management to improve habitat quality for migrating waterfowl. A total of 15 plant species were recorded in plot transect surveys conducted during 1999, none in 2000 and 17 in 2001. Species in the genera Polygonum, Echinochloa, and Cyperus were most common, occurring in > 75% of sample plots. River stage management produced an estimated 2,541 kg ha–1 of moist-soil plant seed in 1999, 0 kg ha–1 in 2000 and 3,336 kg ha–1 in 2001, and seed species composition varied between years. Eighteen species of duck were observed during spring surveys. Duck abundance was lowest in the spring following the failed plant year. Dabbling ducks overwhelmingly used the moistsoil vegetation zone more than open water in 1999 (94.0% of all ducks), and Green-winged Teal Anas crecca, Mallard A. platyrhynchos and Northern Pintail A. acuta spent between 31–46% of their time feeding. River flow management can be used to improve wetland conditions for waterfowl on a large regulated river like the Mississippi.